Alkylimidazolium Ionic Liquids Absorption and Diffusion in Wood - Croitoru, Catalin; Roata, Ionut Claudiu (MDPI- Applied Sciences, 2021)
Ionic liquids represent a class of highly tunable organic compounds responsible for many applications in the domain of wood-based materials. It has often been emphasized that the use of ionic liquids derives from their high affinity for lignocellulose and their good penetration ability into wood structures. This paper discusses the sorption ability of different types of 1-alkyl-3-methylimidazolium ionic liquids with lateral alkyl chains, ranging from ethyl to hexyl into spruce and beech wood, as a function of their cation molecular mass, anion type (chloride, tetrafluoroborate, acetate), and intrinsic properties (surface tension and kinematic viscosity) at room temperature. All the studied ionic liquids present high relative uptake values at the equilibrium, ranging from 11.2% to 69.7%. The bulk diffusion coefficients of the ionic liquids into the wood range from 2 × 10−3 to 28 × 10−3 mm2/min, being higher in the longitudinal direction for both types of wood. The value of the diffusion coefficients for 1-ethyl-3-methylimidazolium chloride is only 25% lower than that for water, despite the obvious differences in viscosity and surface tension, demonstrating a good penetration ability and the potential for wood industry-related applications (as impregnation compound carriers and preservatives).
Keywords: wood; ionic liquids; wood preservatives; diffusion; swelling; lignocellulose